Standard Operating Procedures in the Disorders of Orgasm and Ejaculation. (12th September 2012) - McMahon, Chris G.; Jannini, Emmanuele; Waldinger, Marcel; Rowland, David
ABSTRACT Introduction. Ejaculatory/orgasmic disorders are common male sexual dysfunctions and include premature ejaculation (PE), inhibited ejaculation, anejaculation, retrograde ejaculation, and anorgasmia. Aim. To provide recommendations and guidelines of the current state‐of‐the‐art knowledge for management of ejaculation/orgasmic disorders in men as standard operating procedures (SOPs) for the treating health care professional. Methods. The International Society of Sexual Medicine Standards Committee assembled over 30 multidisciplinary experts to establish SOPs for various male and female sexual medicine topics. The SOP for the management of disorders of orgasm and ejaculation represents the opinion of four experts from four countries developed in a process over a 2‐year period. Main Outcome Measure. Expert opinion was based on grading of evidence‐based medical literature, limited expert opinion, widespread internal committee discussion, public presentation, and debate. Results. PE management is largely dependent upon etiology. Lifelong PE is best managed with PE pharmacotherapy (selective serotonin reuptake inhibitors and/or topical anesthetics). The management of acquired PE is etiology specific and may include erectile dysfunction (ED) pharmacotherapy in men with comorbid ED. All men seeking treatment for PE should receive basic psychosexual education. Graded behavioral therapy is indicated when psychogenic or relationship factors are present and is often best combined with PE pharmacotherapy in an integrated treatment program. Delayed ejaculation, anejaculation, and/or anorgasmia may have a biogenic and/or psychogenic etiology. Men with age‐related penile hypoanesthesia should be educated, reassured, and instructed in revised sexual techniques which maximize arousal. Retrograde ejaculation is managed by education, patient reassurance, and pharmacotherapy. Conclusions. Additional research is required to further the understanding of the disorders of ejaculation and orgasm. McMahon CG, Jannini E, Waldinger M, and Rowland D. Standard operating procedures in the disorders of orgasm and ejaculation. J Sex Med **;**:**–**.